PENGARUH KOMPETENSI PEDAGOGIK DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA SERTA IMPLIKASINYA PADA KINERJA GURU SMK NEGERI DI KABUPATEN KEPULAUAN MERANTI - VINA ERITA; MAHDUM MAHDUM; MURNI BAHERAM (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
The purpose of this research is to know the influence of: 1). Pedagogicalcompetence on the teachers performance; 2). Work Motivation on the teachers performance;3). Job Satisfaction on the teachers performance; 4). Pedagogical competence onjobsatisfaction;5). Work Motivation on job satisfaction; 6). Pedagogical competence and workmotivation simultaneously onjob satisfaction; and 7). Pedagogical competence and workmotivation on teacher performance through job satisfaction.This research was conducted instate vocational schools in island regency meranti by taking the whole stock as a total sample73 teachers.Data collection uses a questionnaire.Research methodology used is the methodsurvey to technique analysis a track (path analysis) with program assistance spss version 20.Theresult of this research is as follows: 1).The contribution pedagogical competence that directlycontribute toteachers performance are 5,24%; 2).Contribution work motivation contribute directlyto teachers performance are 6,00%; 3).The contribution of job satisfaction directly workcontribute to teachers performance are 21,9%; 4).The contribution of pedagogical competencethat directly contribute to job satisfaction are 21,7%; 5).Contribution work motivation that directlycontribute to job satisfaction are 11,6%; 6).The contribution of pedagogical competence andwork motivation that affects job satisfaction are 43,7%; and 7).The contribution of pedagogicalcompetence, work motivation and job satisfaction work simultaneously that influences theperformance are 7,00%.